Physiological responses of Pocillopora corals to upwelling events in the Eastern Tropical Pacific - Castrillón-Cifuentes, Ana Lucia; Zapata, Fernando A.; Wild, Christian (Frontiers in Marine Science, 2023)
Upwelling events can change the sea water conditions within few hours during several months on a seasonal regimen. These events are predicted to intensify due to climate change, exposing shallow benthic organisms to hypoxia and thermal stress, among other extreme conditions. Some coral reefs in the Eastern Tropical Pacific (ETP) recurrently experience upwelling events. Coral reefs off Gorgona Island, Colombia, are exposed to lower oxygen concentrations (3.0 - 3.7 mg O2 L-1) and lower temperatures (17 - 24°C) from mid-January to mid-April, when upwelling develops, compared to the rest of the year (4.9 ± 0.7 mg O2 L-1, 28.4 ± 0.3°C, mean ± SD). While no visible signs of stress have been reported for corals during upwelling, it can be hypothesized that corals would be negatively affected by these changes. Therefore, the objectives of this study were to (1) identify the effects of temperature and hypoxia on the metabolic rate (MO2) of Pocillopora corals under lab conditions, and (2) to examine the changes in skeletal growth and Symbiodiniaceae density of Pocillopora in the field between upwelling and non-upwelling seasons. Findings revealed that MO2 was significantly reduced by 20% at 24°C and significantly increased by 10% at 32°C compared to 28°C. During the upwelling season, Pocillopora corals exhibited a 52% increase in Symbiodiniaceae density, but the growth rate decreased by 50% compared to the non-upwelling season. Fast changes in water conditions during the upwelling strongly affects the metabolism of Pocillopora corals. Although conditions during upwelling were not lethal, they compromised the energy of the coral for their vital functions, indicating that upwelling pushes them toward their physiological limit. Consequently, predicted increases in upwelling events in combination with ocean warming and deoxygenation may be particularly critical for upwelling-exposed corals and the reefs they build in the Eastern Tropical Pacific.